Risposte

2014-01-02T20:22:25+01:00
(x-2+3x)-3(-x+2)=5x+1                                                                                                (4x-2)-3(-x+2)=5x+1                                                                                                    4x-2+3x-6=5x+1                                                                                                         7x-8=5x+1                                                                                                                 7x-5x=1+8                                                                                                                 2x=9                                                                                                                          x=9/2